Direct Observation of Contact Electrification Effects at Nanoscale Using Scanning Probe Microscopy - Jong Hun Kim; Jinhyeok Jeong; Dae Sol Kong; HongYeon Yoon; Hunyoung Cho; Jong Hoon Jung; Jeong Young Park (Advanced Materials Interfaces, 2024)
Abstract In the last decade, contact electrification has gained attention for its potential in energy harvesting, addressing fundamental physics. Scanning probe microscopy (SPM) has evolved as a powerful platform, enabling the in situ characterization/manipulation of a sample's tribological/electrical properties at nanoscale. However, although both the sliding and tapping modes are available in the energy harvesting, the lateral sliding using contact mode SPM has predominantly been employed in triboelectric study. In this work, contact electrification on polydimethylsiloxane is investigated, using peak force tapping atomic force microscopy (PF‐AFM). As PF‐AFM quasi‐discretely offers vertical tapping motions of the probe with a regulated force amplitude, resembling a vertical‐type triboelectric nanogenerator, while minimizing lateral forces. The subsequent surface potential measurements reveal that the generated tribocharge is influenced by both the effective work function difference and energy dissipation at the interface. Furthermore, the accumulation of transferred charges is explored by measuring tip‐sample current during the PF‐AFM operation, showing the comparable results with the surface potential measurement. The results can be attributed to the contact potential difference assisted by the energy dissipation at the interface. This study offers an advanced opportunity to understand and study charge generation behavior based on surface properties without damaging the sample.